Advantages and disadvantages of technological implementation in archive systems: A systematic literature review - Saputra, Dimas; Silvana, Hana; Khoerunnisa, Lutfi (Record and Library Journal, 2024)
Background of the study: In the rapidly developing digital era, the implementation of technology in archival systems has become inevitable. Archive systems are no longer limited to storing physical documents on shelves or filing cabinets, they have evolved into complex and integrated digital systems. Purpose: This research aims to investigate the benefits and disadvantages of implementing technology in archive systems. Method: This research uses a Systematic Literature Review (SLR) approach to identify and analyze relevant articles about the implementation of technology in archive systems. This research is limited to articles published in the last five years in the Scopus database. Findings: The findings of this research reveal that the implementation of technology in archive systems provides significant benefits in terms of efficiency and information accessibility. However, it also presents risks and challenges such as high implementation costs, vulnerability to information security breaches, and risk of data loss. Conclusion: Although the implementation of technology in archival systems promises many benefits, organizations must carefully consider the associated risks and challenges. By better understanding the implications of these steps, organizations can make better decisions in their records management.